2005
DOI: 10.1111/j.1365-2362.2005.01500.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and cardiovascular risk: the role of vascular NAD(P)H oxidase and its genetic variants

Abstract: Several risk factors for coronary artery disease (CAD) induce atherosclerosis through endothelial activation and dysfunction, and ample evidence now suggests that the balance between production and removal of reactive oxygen species (ROS) -a condition termed oxidative stress -is implicated in such processes. A main source of ROS in vascular cells is the reduced nicotinamide adenine dinucleotide/nicotinamide adenine dinucleotide phosphate (NAD(P)H) oxidase system. This is a membrane-associated enzyme, composed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(47 citation statements)
references
References 65 publications
2
43
0
2
Order By: Relevance
“…More detailed analysis of the roles of Ki-ras2A signaling in VSMC proliferation, senescence and phenotypic changes could contribute to further understanding of the pathogenesis of vascular remodeling. It has been suggested that oxidative stress plays a role in the onset and pathogenesis of cardiovascular diseases [37], involving cellular senescence [17,18] and activation of Ras [38]. Moreover, accumulating evidence suggests that Ang II and Aldo mediate oxidative stress by activating NADPH oxidase, which results in superoxide production [13,14,16].…”
Section: Discussionmentioning
confidence: 99%
“…More detailed analysis of the roles of Ki-ras2A signaling in VSMC proliferation, senescence and phenotypic changes could contribute to further understanding of the pathogenesis of vascular remodeling. It has been suggested that oxidative stress plays a role in the onset and pathogenesis of cardiovascular diseases [37], involving cellular senescence [17,18] and activation of Ras [38]. Moreover, accumulating evidence suggests that Ang II and Aldo mediate oxidative stress by activating NADPH oxidase, which results in superoxide production [13,14,16].…”
Section: Discussionmentioning
confidence: 99%
“…Although polymorphisms that affect key pro-and antioxidant enzymes might alter the susceptibility to oxidative stress-mediated injury, the use of genetic epidemiology for the study of oxidative stress-related genes has received little attention in ARF (10,11). Whereas a number of polymorphisms of oxidant stress-related genes might be functionally relevant in human disease (29), we chose to evaluate the genetic variants of two key leukocyte-and endothelium-associated enzymes: NADPH oxidase and catalase. Given its importance in generating superoxide during the respiratory burst of neutrophils, one might anticipate that polymorphisms that disrupt the function of NADPH oxidase would alter oxidative stress-mediated injury in conditions such as ARF.…”
Section: Discussionmentioning
confidence: 99%
“…Potentially relevant SNPs in the p22 phox gene include an Ala174Val polymorphism (33% allelic frequency) and a His72Tyr polymorphism (29% allelic frequency) (217,821). The latter polymorphism is caused by a C to T substitution and is often also referred to as the C242T polymorphism (693).…”
Section: Subunits and Regulatory Proteinsmentioning
confidence: 99%